ON THE ORIGIN OF HIGH ENERGY $γ$-RAYS FROM GIANT RADIO LOBES OF CENTAURUS A - Sahakyan, N.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
Recently the Fermi LAT collaboration reported on the detection of high energy $γ$-ray signal from giant lobes of the radio galaxy Centaurus A. It is shown that if the $γ$-rays had originated from the inverse-Compton scattering of cosmic microwave background photons for the equipartition magnetic field of 2 μG, the Fermi LAT would not detect $γ$-rays from the lobes of Centaurus A. However, the detected $γ$-rays may be produced in hadronic interactions, namely in interactions of high energy protons with low density plasma followed with the production of pions, the neutral component decaying into 2 $γ$-quanta. In this article we study the hadronic origin of $γ$-rays, and estimate the total energy of protons assuming a power-law proton distribution with an exponential cut-off.
Keywords: Centaurus A; radio galaxy lobes; $γ$-rays